On Creation, Nature, and the Ethical Self: a Comparative Analysis of Ikhwān al-Ṣafāʾ, al-Rāghib al-Iṣfahānī, and Abū Ḥāmid al-Ghazālī = ʿn ālḫalq ūālṭbīʿa ūālḏāt ālāʾḫlāqīa: tḥlīlun mqārnun lāʾfkār āʾḫūāni ālṣfāʾ ūālrāġbi ālāʾṣfhānī ūāʾbī ḥāmd ālġzālī - Al-Daghistani, Sami (Journal of Islamic ethics, 2025)
In this paper, I examine ideas on creation, nature, and the ethical self as conceptualized by the Ikhwān al-Ṣafāʾ (Brethren of Purity, fl. ca. 350-369/961-980) and al-Rāghib al-Iṣfahānī (d. before 409/1018), with a particular focus on Abū Ḥāmid al-Ghazālī (d. 505/1111). Drawing from the classical scholarship on kalām, taṣawwuf, and falsafa, I analyze texts by these ethicists who wrote on nature and the role of the human as part of their ethical understanding of the universe as a means to achieve salvation in the Hereafter. By cross-referencing the abovementioned classical scholars and their ideas, I ask how nature is conceptualized in the classical Islamic tradition as part of the divine creation and how closely it was conceived in relation to obtaining a virtuous character. Looking at these three figures who show a degree of cross-influence, indicates that these scholars wrote on creation and nature from an integrative perspective, encompassing theological, philosophical, and cosmological questions as ethical concerns. Reading these scholars presupposes that nature was not separated from other domains but rather amalgamated in a web of approaches and movements that addressed, for instance, the creation of the cosmos and its conservation based on a utilitarian perspective that was nonetheless ingrained in a metaphysical understanding of the universe. In a similar vein, this paper invites us to rethink the contemporary designations of nature/environment as a monovalent concept, encapsulated in a particular division of sciences as it appeared in modern Europe, and hence welcomes a critical take on the current debates on environmental sustainability as a common ethical concern.